Process for regeneration of ore leftovers - CHENG MINGLIANG; MA ZHITONG; ZHANG YONG (2015)
A process for regeneration of ore leftovers comprises the following steps: (1) selecting natural marbles and leftovers and scraps of granite manufacturers as main materials and adopting cement and water as batches; (2) throwing the main materials into crushing equipment to be crushed, then sorting the crushed main materials, throwing the qualified main materials into automatic blending equipment, adding cement and water, and stirring in stirring equipment; (3) after stirring, throwing the raw materials into static molding equipment, and performing extrusion molding by the static molding equipment to prepare products of different specifications; (4) stacking and curing the semi-finished products, wherein curing is carried out by three-stage temperatures, in the first stage, curing is conducted for 7 days at the temperature of 10-20 DEG C, in the second stage, curing is conducted for 15 days at the temperature of 0-10 DEG C, and in the third stage, curing is conducted for 20 days at the temperature of 0-10 DEG C; (5) after curing, planing, polishing and waxing to obtain the end product. The ore leftovers serve as kerbs and pavers, and natural marbles, granite leftovers and scraps are recovered and reutilized, so that waste of secondary resources is avoided.